11.34: Cross‐aisle seismic behaviour of drive‐in rack systems. (13th September 2017) - Shaheen, Mahmoud S.A.; Rasmussen, Kim J.R.
ABSTRACT: This paper presents the results obtained from a comprehensive series of earthquake tests carried out on fully loaded drive‐in steel storage racks. The earthquake waveforms used are actual ground motion records obtained from various locations around the world. The ground motions were applied in the cross‐aisle direction, in which the frames are made of a series of couples of uprights interconnected by diagonal braces to form upright frames. The upright frames were fully braced from top to bottom, and presented the most commonly used system configuration in the industry. In the tests, the 3D structural response was recorded to understand the global behaviour of drive‐in rack systems. The paper also presents the sequence of failures of different components that occurred during the tests, and the impact of these on the system behaviour.